Preparation and Conductive and Electromagnetic Properties of Fe3O4/PANI Nanocomposite via Reverse In Situ Polymerization. (5th December 2019) - Zhang, Di; Chen, Huaiyin; Hong, Ruoyu
Abstract : In this paper, the magnetite/polyaniline (PANI) nanocomposite was prepared by the novel reverse in situ polymerization method. Fe3 O4 magnetic nanoparticles were synthesized in situ in PANI chloroform solution to form a suspension containing the Fe3 O4 /PANI nanocomposite. It overcame the disadvantage of oxidation of the Fe3 O4 by the oxidant in conventional method. The Fe3 O4 /PANI chloroform suspension and the Fe3 O4 /PANI powder were characterized by FT-IR, TEM, XRD, vibrating sample magnetometer, Gouy magnetic balance, conductivity meter, and vector network analyzer. It is demonstrated that the Fe3 O4 /PANI suspension has a good electrical conductivity that is up to 2.135 μ S/cm at the optimal ratio of reactants. The Fe3 O4 nanoparticles are well dispersed in the PANI network with a particle size of about 10 nm. Fe3 O4 /PANI powder has high saturation magnetization and magnetic susceptibility, as well as a broad application prospect in the field of electromagnetic devices. The Fe3 O4 /PANI powder exhibits an excellent microwave absorption behavior, which can be an outstanding candidate for the rapid development of broadband shielding materials.